An error indicator for finite difference methods using spectral techniques with application to aerofoil simulation. (30th May 2018) - Jacobs, Christian T.; Zauner, Markus; De Tullio, Nicola; Jammy, Satya P.; Lusher, David J.; Sandham, Neil D.
Highlights: An error indicator for detecting insufficient numerical resolution is introduced. The indicator is based on spectral techniques using small-domain Fourier transforms. Application to an aerofoil shows how resolution can be targeted more effectively. Abstract: This work introduces a new error indicator which can be used to determine areas of insufficient numerical resolution in unfiltered finite difference simulations. The background behind the methodology is that smaller scales (i.e. the flow features with higher wave numbers) are physically characterised by a smaller energy content in comparison with larger scales. This energy should decrease with increasing wavenumber at a minimum rate; if this rate is not attained it likely means that the smaller scales are not being properly resolved on the computational grid of solution points. An approach using spectral techniques is used to formulate two varieties of the error indicator – one integer-valued and one floating point-valued. These values are computed at a finite number of 'blocks' which span the domain. The indicator is implemented within the OpenSBLI finite difference-based modelling framework, and evaluated in the context of a three-dimensional Taylor-Green vortex problem and flow past a V2C laminar flow aerofoil.